A novel co-treatment scheme for waste motor oil and low rank coal slime: Waste dispose waste. (15th May 2021) - Yang, Zhe; Liao, Yinfei; Ren, Hourui; Hao, Xiaodong; Song, Xingwei; Liu, Zechen
Graphical abstract: Highlights: A novel co-treatment pattern scheme for waste motor oil and low rank coal. Low rank coal slime flotation is improved by the waste motor oil collector. Co-treatment pattern is economically profitable and environmentally controllable. Abstract: Waste motor oil (WMO) is a hazardous oil pollutant in the automobile industry and low-rank coal slime (LRCS) is a solid waste produced during coal preparation. This paper introduces a comprehensive utilization scheme for these two waste resources through froth flotation. Fourier Transform Infrared Spectroscopy (FTIR) measurement showed that WMO contains hydrocarbons and their oxides (alkane, aromatic derives, ester or carboxylic acid). When acting as a collector for the flotation of LRCS, WMO resulted in a cleaned coal yield of 77.29% and an ash content of 8.97% at the dosage of 5 kg/t, which was a significant improvement over the traditional collector, diesel oil. A novel co-treatment scheme for WMO and LRCS was proposed and discussed. The co-treatment scheme can bring high quality products for the coal preparation plant and give an alternative of disposing the WMO. The traditional WMO disposal methods like WMO regeneration may produce secondary pollution while the co-treatment scheme has little and controllable environmental impact. What's more, the scheme has better economic benefit than LRCS flotation using diesel oil or the WMO traditional disposal method.